Strategi Marketing Komunikasi Media Online Detik.com - Syuhada, Imam Bagus (Universitas Prof. Dr. Moestopo (Beragama), 2012)
Advertising is essential to be able to promote a product or service, so that people know and know what productsand services they need are .. The emergence of new media (new media) or digital media that combines Internettechnology, audio-visual and mobile, felt increasingly threatened the existence of the conventional media.Detik.com is a web portal that provides the latest news and articles online in Indonesia. AFP has only an onlineedition and hung from the field of advertising revenue. Even so, the AFP is at the forefront of new news (breakingnews).In this study, the problems to be discussed by the researchers that Online Media Marketing Strategy Detikcom.In this study, researchers focused on marketing communications strategies that run Detikcom as the first onlinemedia in Indonesia in order to survive with the emergence of online media as a new-media online Detikcom competitors.The goal is to determine the marketing communication strategies used to address the media Detikcomonline competitors.Paradigm used in this study is constructivism paradigm. This paradigm is used because researchers participatedin the construction of social reality of the problems studied.The theory used is the theory of marketing communication system which emphasizes that the 5 components in thetheory (key factor analysis, promotion objectives, positioning, communication budgets, and research and evaluation)should be clear and work well for the achievement of marketing objectives Detikcom.This research is qualitative. A qualitative approach is considered appropriate for this study because the researcherswanted to see how the overall marketing strategy Detik.com and process-oriented, instead of measuring thesuccess of the strategy.This is a descriptive study, which aims to provide a complete picture of the stages and the relationships containedin the marketing activities Detikcom.The results showed that, first, the emergence of mobile applications has been running effectively since it is supportedon the sophistication of todays technology. Second, at the moment all online media rely on the power toattract news readers, Detikcom actually issued several channels that are reaching young people. This is done sothat the level of traffic AFP remained at the top position. Third, these canals have different ways of promotion, oneof them with a media partner at events such as music concerts, sporting events, and free holiday.